Ungkapan Larangan Masyarakat di Kanagarian Inderapura Kecamatan Pancung Soal Kabupaten Pesisir Selatan - Rosmina, Rosmina; Abdurahman, Abdurahman; Tamsin, Andria Catri (Universitas Negeri Padang, 2013)
The study aims to describe and analyze the expression of the ban, meaning rationalization, and social functioning ban public expression in Kanagarian Inderapura Kecamatan Pancung Soal Kabupaten Pesisir Selatan. The data source of this research is oral sources. Oral sources, which ban the phrase spoken by people in communication obtained through interviews. Data collection using interviews, records, and record. Recording method used to record all information submitted informant. The method used to record record important information obtained from informants. Based on the study concluded the following. First, in the expression of 79 found expression prohibition Prohibition. Second, in the expression of the social restrictions found expression prohibition 3 functions, namely remind, prohibit, and educate. Third, the prohibition contained in the expression of the meaning of rationalization. The phrase is also called superstition ban because it involves a mystical belief.